A study on stability of fill on clay subsoil - Tezulaş, Eser. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1982., 1982)
The procedures, assumptions and equilibrium methods used to develope the slope stability charts and detailed analysis procedures of stability are investigated during the first phase of the thesis. The stability of a cohesionless fill on a clay foundation using Ordinary Method Slices and Bishop's Modified Procedures of stability analysis are examined on the second phase of the thesis. For this purpose the effects of the shear strengths parameters of the fill and subsoil clay fondution on tbe factor of safety are investigated. Furthermore the effect of variation in fill unif weight on stability and the stability of the fill on normally consolidated clay foundation those shear strengthis linearly varying with depth are also evaluated. For practical use, charts giving the variations of factor of safety with dimensionless parameters are also developed.|Keywords : Slope stability, fill, clay subsoil.
Keywords: Soil stabilization.; Slopes (Soil mechanics); Soil mechanics.